Iowa Birdline update, July 4, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for July 4, 1994 Highlights of the update include sightings of Yellow-breasted Chats, a Northern Mockingbird, a Pileated Woodpecker, a Common Tern, and an early returning Willet. Also of note were observations of several species of Warblers as well as two Ringed-turtle Doves visiting a feeder at Swaledale. Epson - sheet feed/flatbed